PENGARUH JOB STRESS TERHADAP KOMITMEN ORGANISASIONAL DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI - Yanuar Fajar Nugroho (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
The purpose of this study were: 1) To analyze the effect of job stress on commitment organizational, 2) To analyze the effect of job stress to work motivation; 3) To analyze the effect of work motivation to commitment organizational 4) To analyze the effect variables of work motivation as a variable intervening in job stress to commitment organizational. The selection of the sample in this study carried out by using survey methods. By using questionnaires as the primary data collection tool. The population of this study were employees of PT. Bank X, Surabaya. The method used is a non-probability sampling method. Analysis tool used is the test of validity, reliability testing, test analysis and Path Analisys. By using statistical analysis with SPSS version 26.0 for windows results of this study indicate that the value from sobel test is 2,021 > 2,000 (t-table), this means participation in work motivation as a variable intervening in job stress directly affect to commitment organizational, further significant job stress on commitment organizational and work motivation can be used as intervening variables in relation of commitment organizational of PT. Bank X Surabaya employee.